1977
DOI: 10.1289/ehp.772133
|View full text |Cite
|
Sign up to set email alerts
|

Interim results of two-year toxicological studies in rats of vinylidene chloride incorporated in the drinking water or administered by repeated inhalation

Abstract: Male and female Sprague-Dawley rats were exposed to vinylidene chloride (VDC) orally or by inhalation in 2-year toxicological studies. Interim results are included in this report. VDC was given in the drinking water at mean ± S.D. concentrations of 0, 68 ± 13, 106 ± 22, and 220 ± 35 ppm which produced mean ± S.D. dosage levels of 0, 5.9 ± 0.6, 10.0 ± 1.2, and 19.3 ± 2.7 mg/kg for male rats and 0, 7.5 ± 0.4, 12.6 ± 1.1, and 25.6 ± 2.4 mg/kg for female rats. Forty-eight rats/sex/VDC level and 80 rats/sex in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1980
1980
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 5 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…The rat liver was refractory to the tumorigenic effects of PCE. In addition to the studies above, additional carcinogenicity studies by Rampy et al (Rampy et al, 1978) and Maltoni and Cotti (Maltoni and Cotti, 1986) have shown a lack of a tumor response in the rat following chronic exposure to PCE (see Table 3). The negative liver tumor response in the rat is valuable in examining possible mechanisms for PCE-induced mouse liver tumors.…”
Section: Chronic Rodent Studies With Pcementioning
confidence: 89%
See 1 more Smart Citation
“…The rat liver was refractory to the tumorigenic effects of PCE. In addition to the studies above, additional carcinogenicity studies by Rampy et al (Rampy et al, 1978) and Maltoni and Cotti (Maltoni and Cotti, 1986) have shown a lack of a tumor response in the rat following chronic exposure to PCE (see Table 3). The negative liver tumor response in the rat is valuable in examining possible mechanisms for PCE-induced mouse liver tumors.…”
Section: Chronic Rodent Studies With Pcementioning
confidence: 89%
“…In chronic studies examining the carcinogenicity of TCA or PCE in the liver, the rat, unlike the mouse, did not show an increase in liver neoplasms (NTP, 1986; JISA, 1993; NCI, 1977; Rampy et al, 1978; Maltoni and Cotti, 1986; DeAngelo et al, 1997) (Table 7). To further define this species difference in tumor induction several studies examined the induction of the PPARα-related PCO activity in the rat after treatment with TCA (Table 7).…”
Section: Activation Of Pparα By Tcamentioning
confidence: 98%
“…The results of a number of long term carcinogenicity tests have recently become avail able, either as preliminary communications or as interim results of on-going studies [4][5][6], The preliminary re sults of one study, in which VDC was given by inhala tion, point to the induction of kidney carcinoma in mice and to an increased incidence of mammary tumours in rats, no carcinogenic effect was observed when VDC was administered by the oral route to rats or hamsters [4], An increased incidence of lung, skin and liver cell tumours in mice and the induction of haemangiosarcomas in both mice and rats was reported in another inhalation study [7], In addition, VDC has been shown to be mutagenic to Salmonella typhimurium [8], Chloroprene (CP) is used as a chemical intermediate, mainly as the monomer in the manufacture of synthetic elastomers. World production of this compound in 1977 is estimated to have been 300,000 t.…”
Section: Introductionmentioning
confidence: 99%